2007
DOI: 10.1007/s10592-007-9409-9
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity in adult and seedling populations of Primula vulgaris in a fragmented agricultural landscape

Abstract: Habitat fragmentation is known to generally reduce the size of plant populations and increase their isolation, leading to genetic erosion and increased betweenpopulation genetic differentiation. In Flanders (northern Belgium) Primula vulgaris is very rare and declining. Populations have incurred strong fragmentation for the last decades and are now restricted to a few highly fragmented areas in an intensively used agricultural landscape. Previous studies showed that small populations of this long-lived perenni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
66
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(69 citation statements)
references
References 78 publications
1
66
0
2
Order By: Relevance
“…seedling cohorts (Cabin et al, 1998;Asuka et al, 2004;Caldiz and Premoli, 2005;MandĂĄk et al, 2006;Van Geert et al, 2008;Fuchs and Hamrick, 2010). Importantly, majority of these earlier studies used allozyme markers that might have been directly subject to natural selection, although similar patterns have also been observed in later studies using microsatellite markers (for example, Jones and Hubbell, 2006).…”
Section: Discussionmentioning
confidence: 62%
“…seedling cohorts (Cabin et al, 1998;Asuka et al, 2004;Caldiz and Premoli, 2005;MandĂĄk et al, 2006;Van Geert et al, 2008;Fuchs and Hamrick, 2010). Importantly, majority of these earlier studies used allozyme markers that might have been directly subject to natural selection, although similar patterns have also been observed in later studies using microsatellite markers (for example, Jones and Hubbell, 2006).…”
Section: Discussionmentioning
confidence: 62%
“…Adults and seedlings can also show distinct responses to habitat loss and fragmentation (Van Geert et al, 2008). Genetic variability and differentiation of adults of perennial plants often show responses to past landscape conditions but not to recent habitat changes (Collevatti et al, 2001;Kramer et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Genetic variability and differentiation of adults of perennial plants often show responses to past landscape conditions but not to recent habitat changes (Collevatti et al, 2001;Kramer et al, 2008). Nevertheless, several studies found decreasing genetic variability and increasing inbreeding coefficients in the progeny (seedlings), suggesting that there may be a time lag before ongoing habitat fragmentation is observed in the genetic structure of adults (Kettle et al, 2007;Aguilar et al, 2008;Van Geert et al, 2008). Therefore, assessing genetic variability in seedlings instead of adults in fragmented landscapes is useful when evaluating the ongoing effects of habitat loss and fragmentation on genetic variability and differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…However, empirical studies of small, isolated populations have yielded variable results [9,12]. Cases have been reported in which fragmented populations of some widespread plant species promoted gene flow and were not detrimental [15][16][17]. Several factors responsible for such discrepancy have been proposed such as interspecific longevity differential, pre-fragmentation abundance, different mating system, the presence of seed banks, and interaction of animal population and seed dispersal [12].…”
Section: Introductionmentioning
confidence: 99%